MHD radiative mixed convective flow of a sodium alginate-based hybrid nanofluid over a convectively heated extending sheet with Joule heating - Yasmin Humaira; Bossly Rawan; Alduais Fuad S.; Al-Bossly Afrah; Saeed Anwar (Nanotechnology Reviews)
The study of hybrid nanofluids is significant in thermal management applications by optimizing heat transfer through pioneering materials, mainly the flow of sodium alginate-based hybrid nanofluids. This work addresses the demand for effective cooling solutions in a variety of industrial processes and uses the unique characteristics of non-Newtonian fluids and their inferences for rheological modeling and heat transform enhancement. Inspired by the progressive properties of the non-Newtonian Casson fluid and its applied significance in the rheological modeling and heat transfer characteristics of different dynamic fluids, there is limited knowledge of their response in the mixed convective flow, particularly when influenced by factors like thermal radiation, joule heating, and thermal relaxation time. The present study aims to investigate the heat transfer enhancement of the mixed convective flow of a sodium alginate-based hybrid nanofluid on an extending sheet concentrating on the interaction of different physical parameters that affect thermal performance. The physical phenomena are modeled in a nonlinear partial differential equation, which is then converted into ordinary differential equations with the help of suitable similarity variables. Tables and figures are constructed to show the behavior of the physical parameters involved in the momentum and temperature equations. Premilinary assumptions applied to the flow are electrically conducting, rotating, dissipative, and thermal boundary conditions. A semi-analytical approach homotopy analysis method is employed to obtain the solution of the problem. The outcome witnessed that the velocity profiles show a diminishing behavior through a magnetic parameter; however, the temperature profile shows an escalating behavior. Similarly, the thermal plot intensifies with the Eckert number and thermal radiation. In addition, the numerical data from the tables portrayed that the skin friction decreases with the Casson parameter and the rotation parameter; however, an improvement behavior is noticed in the Nusselt number through thermal radiation and thermal Biot number. From the numerical data, it is concluded that the hybrid nanofluid has superior heat transfer characteristics compared to nanofluid. The finding of this result has also been compared with available results in the literature through a comparative study.